Bibliometrics Literature Revise on Exchange Rate: A Future Research Agenda - Muhammad Naeem; Hammad Ejaz Khan; Raza Ali (ETIKONOMI, 2022)
This study aims to conduct a bibliometric citation and content analysis of the scholarly literature on the behavior and dynamics of the exchange rate (5,295 articles) over the past 85 years between 1935-2020. This research identifies five different research streams such as (i) Dynamics of the exchange rate; (ii) Exchange rate volatility using the autoregressive model; (iii) Relationship between exchange rate and interest rate; (iv) Impact of exchange rate volatility on growth, trade, and investment;  (v) Effects of exchange rate fluctuation on firms earning management. In addition to these research streams, the influential articles, authors, journals, organizations, and countries have been evaluated through network diagrams. Finally, sixteen future research questions have been developed through content analysis. How to Cite:Naeem, M., Khan, H. E., & Ali, R. (2022). Bibliometric Literature Review on Exchange Rate: A Future Research Agenda. Etikonomi 21(1), 41-54. https://doi.org/10.15408/etk.v21i1.22412.